The Effect of Career Specific Parental Behavior on Career Adaptability of Senior High School Students - Virgie Alxandra; Veronica A. M. Kaihatu (proceedings.icesy, 2026)
High school seniors can either start working or continue their higher education, but all decisions made will determine the direction of their careers. Problem arise when their career adaptability tends to be low. Parents have a significant influence on the development of their children’s career adaptability. Parental support, interference, and lack of engagement in the child’s career development process are the specific factors. This research aims to determine the influence of career specific parental behavior on career adaptability in senior high school students. This research uses quantitative methods with logistic regression analysis. The measuring instruments used in this research were the Career Adapt-Abilities Scale-Short Form and Perceived Parental Career-Related Behaviors scale. Data collection is carried out through an online questionnaire. The research results showed that there is an influence of parental support on career adaptability in senior grade high school students (X2 (385)=4,721, p=0,030, R2=0,365), there was no influence of parental lack of engagement on career adaptability (X2 (385)=2,322, p=0,128, R2=0,244), and there was no influence of parental interference on career adaptability (X2 (385)=2,550, p=0,110, R2=0,263). These results show that the higher the level of parental support, the higher the level of career adaptability.